2018
DOI: 10.1038/s41594-018-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational protein assembly imposes evolutionary constraints on homomeric proteins

Abstract: Cotranslational protein folding can facilitate rapid formation of functional structures. However, it might also cause premature assembly of protein complexes, if two interacting nascent chains are in close proximity. By analyzing known protein structures, we show that homomeric protein contacts are enriched towards the C-termini of polypeptide chains across diverse proteomes. We hypothesize that this is the result of evolutionary constraints for folding to occur prior to assembly. Using high-throughput imaging… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 67 publications
4
61
1
Order By: Relevance
“…Co-translational assembly in homomeric proteins can also cause premature assembly of protein complexes, if two interacting nascent chains are in close proximity. Thus, it seems that homomeric protein IDs are enriched toward the C termini of polypeptide chains across diverse proteomes and it has been suggested that this is the result of evolutionary constraints for folding to occur before assembly 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Co-translational assembly in homomeric proteins can also cause premature assembly of protein complexes, if two interacting nascent chains are in close proximity. Thus, it seems that homomeric protein IDs are enriched toward the C termini of polypeptide chains across diverse proteomes and it has been suggested that this is the result of evolutionary constraints for folding to occur before assembly 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the SWI of the full-length sequences has a much stronger correlation with solubility (Spearman's rho = 0.46, P = 2.97 ✕ 10 -19 ; Supplementary Fig S6C). These results suggest that the full-length of sequences contributes to protein solubility, not just surface residues, in which solubility is modulated by cotranslational folding (Natan et al 2018) .…”
Section: Fig 2 Derivation Of the Solubility-weighted Index (Swi) (A)mentioning
confidence: 85%
“…Ordered assembly 263 The time ordering of assembly steps in proteins is integral to the correct assembly of the 264 protein structure. This holds true on many length scales of assembly, with 265 cotranslational protein folding able to induce misassembly [15] all the way up to final 266 quaternary structure as examined here. Experimental methods for devising binding 267 strengths are still being developed [16], with an in silico approach recently introduced 268 focusing on multimeric complexes [17].…”
mentioning
confidence: 79%